MERANCANG PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL DAN BERWAWASAN PLURALIS MULTIKULTURALIS DI SMAN 1 MOGA KABUPATEN PEMALANG - slamet tasdik (Jurnal Penelitian Agama, 2015)
Abstract: The concem of this research is how the social system of Indonesian culture that has a long history to this day, and made up of a variety of factors that influence it. Religious education in schools is still considered dogmatic, less developed the ability to think critically and creatively so that bring out textual and exclusive religious understanding. Religious education through the efforts of a multicultural pluralist approach should be designed and developed an integrated, comprehensive and conceptual, where the design implementation should be based on four devices, namely: curriculum reform, learning the principles of social justice, multicultural competency development, and implementation of educational equality. Keywords: Leaming Design, PAI with Pluralistic and Multicultural Perspective.